The infants’ gut microbiome: setting the stage for the early onset of obesity - Vallès, Yvonne; Arshad, Muhammad; Abdalbaqi, Mamoun; Inman, Claire K.; Ahmad, Amar; Drou, Nizar; Gunsalus, Kristin C.; Ali, Raghib; Tahlak, Muna; Abdulle, Abdishakur (Frontiers in Microbiology, 2024)
In the past three decades, dietary and lifestyle changes worldwide have resulted in a global increase in the prevalence of obesity in both adults and children. Known to be highly influenced by genetic, environmental and lifestyle factors, obesity is characterized by a low-grade chronic inflammation that contributes to the development of other metabolic diseases such as diabetes and cardiovascular disease. Recently, the gut microbiome has been added as a cause/contributor to the development of obesity. As differences in the microbiome between obese and normoweight individuals have been observed, we set out to determine whether infants harbor an obesogenic microbiome early on and whether the pre-pregnancy status of the mother (obese or normoweight) is correlated to their infant’s microbiome composition. Using shotgun sequencing, we analyzed stool samples throughout the first year of life from infants born to obese (n = 23 participants, m = 104 samples) and normoweight (n = 23 participants, m = 99 samples) mothers. We found that the infants’ microbiome diversity at taxonomic and functional levels was significantly influenced by time (ANOVA p < 0.001) but not by the mother’s pre-pregnancy status. Overall, no deterministic succession of taxa or functions was observed. However, infants born to obese mothers were found to have a significantly higher Bacillota/Bacteroidota ratio (p = 0.02) at six months, were significantly depleted from six months old of the well-established obesity biomarkers Akkermansia municiphila and Faecalibacterium prausnitzii (p < 0.01), and were at one week old, significantly enriched in pathways such as the UDP-N-acetyl-D-glucosamine biosynthesis II (p = 0.02) involved in leptin production, suggesting perhaps that there may exist some underlying mechanisms that dictate the development of an obesogenic microbiota early on.